Response of mineral mixture, prajana and GnRH on serum biochemical constituents and conception rate in anoestrus buffalo - SINGH, A P; SAH, R S; SINGH, R B; AKHTAR, M H; ROY, G P; SINGH, C; KUNJ, VIVEK (The Indian Journal of Animal Reproduction, 2023)
The serum biochemical constituents (calcium, inorganic phosphorus, total serum protein, blood glucose and alkalinephosphatase) concentration in cycling buffaloes were significantly (P < 0.05) higher than non cycling buffalo. Out of30 anoestrusbuffalo cows treated with supplevite -M , 14 ( 16.66%) showed estrus after 30 days treatment, IO buffalo (71.42%) conceived.Out of 32 buffalo heifers 24 were anoestrus and the 8 were under normal cyclic. The anoestrus animals were treated withsupplevite-M, at the rate of25 gm/day per animal twice daily for 30 days. The blood biochemical profile ofnormal cycling as wellas treated animal was done on 0, 15, and 30th day. No significant difference was noted in serum biochemical constituents in cyclinganimal while in treated anoestrus animal all the parameters studied and found to be significant.
Keywords: Anestrus; serum biochemical; GnRH; Prajana; mineral mixture